PENGARUH SOSIAL EKONOMI TERHADAP STATUS GIZI KURANG PADA BALITA DI KECAMATAN PURWODADI KABUPATEN GROBOGAN : Array - Kiki Natassia (Yayasan Citra Dharma Cindekia, 2022)
Malnutrition is a condition where the nutritional needs of the body are not met within a certain period of time. Malnutrition is a major health problem worldwide. Globally, according to WHO, from data from around the world in 2018, around 7.3% or 49 million children under five years of age were undernourished. The prevalence of under-five children with malnutrition status in Indonesia is 13.8% and in Central Java Province the prevalence of under- nutrition is 14.0%. While in Grobogan Regency, it is known that there are 744 toddlers who experience malnutrition. This study aims to determine the effect of socio-economic on the nutritional status of under-fives in Purwodadi District, Grobogan Regency. The design in this study used a comparative descriptive and Case Control approach. The sampling technique used in this study was non- probability sampling with a total sampling method, and obtained 66 respondents, with 33 respondents in the case group with poor nutritional status and 33 respondents in the control group with good nutritional status. From the Chi- Square socio-economic test with poor nutritional status in toddlers, it is known that the p-value is 0.000 < 0.05 at 95% significance where ho is rejected, ha is accepted. So it can be concluded that there is a socio-economic influence on the nutritional status of under-fives in Purwodadi District, Grobogan Regency. There is a socio-economic influence on the nutritional status of under-fives in Purwodadi District, Grobogan Regency